The Influence of Educational Videos as an Effort to Improve Cadre Attitudes in Cervical Cancer Prevention in Wijimulyo Village, Nanggulan, Kulon Progo: PENGARUH VIDEO EDUKASI TERHADAP SIKAP KADER DALAM MENCEGAH KANKER SERVIKS - endar Timiyatun Timiyatun; Eka Oktavianto; Pipin Nurhayati (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2026)
Introduction: Efforts to improve cervical cancer prevention through health education are a simple form of health promotion that can reach a wide range of targets. Health education provides and enhances knowledge, which in turn can improve attitudes toward maintaining and improving public health, such as cervical cancer prevention. Attitude changes are influenced by knowledge and information that can be obtained from various sources, including health education and counseling. Objective: This study aims to determine the effect of educational videos on the attitudes of community health workers (cadres) in preventing cervical cancer. Research Methods: This study was quantitative with a pre-experimental design. Sampling used simple random sampling, with 25 community health workers. This study was conducted in the Wijimulyo area, Nanggualn, Kulon Progo. The research instruments used educational videos and attitude questionnaires. The paired t-test was used for analysis. Results: The results showed an increase in the average attitude score from 70.72 to 91.04 with a p-value of 0.000 (p<0.05), indicating a significant effect of educational videos on community health workers' attitudes toward cervical cancer prevention. Conclusion: Providing education using a cervical cancer education video is very effective in improving cadre attitudes towards cervical cancer prevention. Suggestion: The cadre coordinator should coordinate with the health office and community health centers to improve cadre knowledge and training in cervical cancer prevention.